"Still in the Game": Cybertransformations of the "New Flesh" in David Cronenberg's eXistenZ. - Hotchkiss, Liam M. (Velvet Light Trap: A Critical Journal of Film & Television)
Examines David Cronenberg's science fiction motion picture "eXistenZ," which explores the relationship between virtual reality games, art, fantasy and real life. Connection between "eXistenZ" and "Videodrome"; Ontology of cyberculture; Differences in the treatment of Plato's allegory of the cave in "The Thirteenth Floor," The Matrix" and "eXistenZ."